Antioxidant Role of PcGSTd1 in Fenpropathrin Resistant Population of the Citrus Red Mite, Panonychus citri (McGregor) - Liao, Chong-Yu; Feng, Ying-Cai; Li, Gang; Shen, Xiao-Min; Liu, Shi-Huo; Dou, Wei; Wang, Jin-Jun (Frontiers in Physiology, 2018)
The citrus red mite, Panonychus citri, a major citrus pest distributed worldwide, has evolved severe resistance to various classes of chemical acaricides/insecticides including pyrethroids. It is well known that the resistance to pyrethroids is mainly caused by point mutations of voltage-gated sodium channel gene in a wide range of pests. However, increasing number of evidences support that pyrethroids resistance might also be resulted from the integrated mechanisms including metabolic mechanisms. In this study, firstly, comparative analysis of RNA-seq data showed that multiple detoxification genes, including a GSTs gene PcGSTd1, were up-regulated in a fenpropathrin-resistant population compared with the susceptible strain. Quantitative real time-PCR results showed that the exposure of fenpropathrin had an induction effects of the transcription of PcGSTd1 in a time-dependent manner. In vitro inhibition and metabolic assay of recombinant PcGSTd1 found that fenpropathrin might not be metabolized directly by this protein. However, its antioxidant role in alleviating the oxidative stress caused by fenpropathrin was demonstrated via the reversely genetic experiment. Our results provide a list of candidate genes which may contribute to a multiple metabolic mechanisms implicated in the evolution of fenpropathrin resistance in the field population of P. citri. Furthermore, during the detoxification process, PcGSTd1 plays an antioxidant role by detoxifying lipid peroxidation products induced by fenpropathrin.